2023
DOI: 10.1002/cite.202200230
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Temperature‐Dependent Activity Coefficients at Infinite Dilution Using Tensor Completion

Abstract: Knowledge of thermodynamic properties of mixtures is essential in many fields of science and engineering. However, the experimental data is usually scarce, so prediction methods are needed. Matrix completion methods have proven to be very successful in predicting thermodynamic properties of binary mixtures. In this approach, the experimental data is organized in a matrix whose rows and columns correspond to the two components, and whose entries indicate the value of the studied thermodynamic property at fixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This phenomenon aligns with expectations, as extrapolating to new solvents within polymer–solvent mixtures presents a more challenging task compared to interpolating among known chemical species. This can be confirmed, by the fact that interpolation can even be approached (with remarkable accuracy) using matrix or tensor completion techniques that do not need explicit chemical structure insights. …”
Section: Results and Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This phenomenon aligns with expectations, as extrapolating to new solvents within polymer–solvent mixtures presents a more challenging task compared to interpolating among known chemical species. This can be confirmed, by the fact that interpolation can even be approached (with remarkable accuracy) using matrix or tensor completion techniques that do not need explicit chemical structure insights. …”
Section: Results and Discussionmentioning
confidence: 91%
“…This can be confirmed, by the fact that interpolation can even be approached (with remarkable accuracy) using matrix or tensor completion techniques that do not need explicit chemical structure insights. 43 45 …”
Section: Results and Discussionmentioning
confidence: 99%
“…Within KEEN, these methods have been complemented with physical knowledge [18,19] and were applied to different physical properties [20,21]. In this special issue, matrix-completion is generalized to tensor completion techniques [43]. It is shown that this allows to systematically extract information on the dependence of mixture properties on a physical variable, e.g., temperature.…”
Section: Modeling and Simulationmentioning
confidence: 99%
“…The crux of MCMs lies in their proficiency in inferring missing entries by identifying patterns within the matrix and leveraging similarities across rows and columns. Recent explorations, such as those by Jirasek et al, 16 Damay et al, 17 and Chen et al, 18 have applied MCMs to predict γ values in both traditional solvent systems and ionic liquid (IL) systems, demonstrating the method's versatility. For instance, Jirasek et al 16 applied a MCM for predicting infinite dilution γ values (γ ∞ ) at ambient temperature, showing favorable performance compared to UNIFAC.…”
Section: Introductionmentioning
confidence: 99%